Management practices of selected credit cooperatives - Dumocmat, Joselito O. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2021)
This sequential explanatory research aimed to assess and analyze the extent of management practices along Organizational and Management, Operations, Marketing, and Finance among teachers' credit cooperatives earlier found by the Cooperative Development Authority - Regional Office 1 as non-compliant. The respondents were the cooperatives' key officers and members. Quantitative data were gathered using a survey questionnaire; the results of which were subsequently used in gathering the qualitative data through individual interviews. The extent of practice of management systems of the cooperatives was found that various problems were encountered in the management of the cooperatives. The study concluded that the cooperatives had management issues that need to be addressed. Based on the findings and conclusions, a strategic management framework and a strategic plan were crafted and proposed for the efficient and effective operation of ccoperatives and thus help prevent breakdown.
References: pages 111-121.
CHED-La Union
Keywords: Cooperatives